Application of resilience model for flood management in local planning context / Zulkifli Ahmad Zaki …[et al.] - Ahmad Zaki, Zulkifli; Abdullah, Yusfida Ayu; Yusup, Mohammad; Che Abdullah, Ishak (Universiti Teknologi MARA, 2021)
Combination of rapid urbanisation and climate change likely results in significantly larger flood impact compared to the previous flood events. Complexity in urbanisation process and uncertain climate factor are the main challenges faced by urban planners in developing a safe and less vulnerable city. The existing traditional flood management depends on the flood-control measure cannot cope with the emergent flood. In this context, the concept of resilience gained much attention as a relatively new approach in urban areas. This paper therefore presents a study on the application of resilience model for flood management in urban areas. Kuala Lumpur which is located at the Southeast Asia region was chosen as the case study due to its compact urban area and densely populated. A case study method and qualitative approach were employed in conducting the study. Results obtained from the study revealed that Kuala Lumpur had not extensively practice a comprehensive urban flood management approach based on the resilience model. However, the intention to change from typical and conventional measures into resilience and holistic approach is evident and promising.